Membangun Karakter Remaja Yang Positif Dengan Edukasi Bahaya Sex Bebas Pada Remaja - Nurlela Hi. Baco; Bayu Dwisetyo; Novita Pesak; Vrigia Lumeohe; Febi Sabanari (Compromise Journal Community Proffesional Service Journal, 2024)
Free Sex is a sexual behavior conducted without commitment and without considering the long-term consequences, which is often experienced by teenagers. High social pressures, lack of understanding about reproductive health, and the influence of social media are the main factors that exacerbate this behavior. Education about the dangers of free sex in teenagers is crucial to reduce the rates of unintended pregnancies, sexually transmitted infections, and other psychological impacts. This community service activity aims to increase teenagers' understanding and awareness about the dangers of free sex and to instill a healthy lifestyle in maintaining responsible sexual relationships. The method used was counseling through a presentation using PowerPoint media, followed by a question-and-answer session with students from SMP N1 Tumpaan, South Minahasa District. This activity was held on January 4, 2025, with the hope of having a positive impact on teenagers' behavior in maintaining their reproductive health.